Analisis Swot terhadap Strategi Marketing Bank CIMB Niaga Syariah dalam Meningkatkan Penjualan Produk Haji Periode 2020-2023 : Studi Pada Kantor Kementrian Agama Kota Surabaya - Juairiah Juairiah; Dewi Riza Lisvi Vahlevi (Journal of Management and Creative Business, 2024)
Islam encourages its people who are able to perform the Hajj pilgrimage. This research aims to find out and analyze the marketing strategies used in Bank CIMB Niaga Syariah's Hajj savings products. In this research, SWOT analysis was used by looking at the results of existing data so that it was able to increase sales of Hajj savings products. The research approach used in this research is a descriptive qualitative approach. From the results of the analysis, it can be seen that the marketing strategy implemented is said to provide sufficient effective value in this research. And analysis was carried out in the form of a SWOT analysis resulting in growth in sales of Hajj savings products in safe conditions in terms of market share. This strategy indicates that Bank CIMB Niaga Syariah is quite capable and strong in expanding sales of its Hajj savings products.